Persian Vowel Production in Hearing-Impaired Children With Cochlear Implants: The Influence of the Implantation Age - Mahdi Sarayani; Amir Poursadegh; Reyhane Mohamadi (Function and Disability Journal, 2021)
Background and Objectives: Speech intelligibility is affected by vowel quality. Auditory feedback is an essential factor in vowel quality. The purpose of the current study was to compare vowel space and formant frequencies in Normal-Hearing (NH) and Cochlear-Implanted (CI) Persian-speaking children aged 4 to 6 years. Methods: The participants were 10 CI children (5 girls and 5 boys) aged 4 to 6 years. All children had congenital hearing loss and received a multichannel CI before 2 years of age. The control group comprised 20 NH children (10 girls and 10 boys) aged 4 to 6 years. The two groups were matched by age. The participants were asked to produce six Persian vowels (/u/, /o/, /a/, /i/, /e/, /æ/) in /ChVCd/ context and then the average of formant frequencies (F1, F2,) was measured using Praat analysis software (Version: 5, 3, 27). The Independent samples t-test was conducted to assess the differences in F1 and F2 values between the two groups using SPSS 16. Results: The mean values of F1 and F2 of all 6 Persian vowels were not significantly different between CI and NH children (P>0.05). Conclusion: Findings of the present study implied that children who were implanted CI under 2 years of age are likely to produce Persian vowels similar to normal-hearing children.